IMPROVING STUDENTS’ WRITING SKILLS OF NARRATIVE TEXT THROUGH BRAINSTORMING TECHNIQUE - kurnia budiyanti (Al-Manar : English and Arabic Journal, 2014)
The researcher found that students had low ability in writing narrative text. It was identified that there were several factors that caused students had low ability. From the students themselves, they did not know how to start their writing because they did not apply certain technique. Then, they also get it difficult to express their ideas in written form. Furthermore, they got lack of vocabulary, lack understanding of gramatical devices, organization and mechanism in writing.To improve the students’ ability in writing Narrative text, the researcher conducted classroom action research by using Brainstorming Technique. The purpose of this research is to find out whether Brainstorming Technique could better improve students’ writing ability and to find out factors that influence it. In collecting the data, the researcher used essay tests, observation checklist, field notes, and interview. This classroom action research consisted of three cycles constituting meeting. Based on the finding, the implementation of Brainstorming Technique could better improve students’ skill in writing Narrative text at the second year students of State Islamic University Suska Riau. The improvement was shown by the increasing of the percentage of students’ writing tests from cycle 1 to cycle 2, and from cycle 2 to cycle 3. The factors influenced the students’ ability in writing Narrative text were the indicators of Brainstorming Technique itself. Finally, the action research by the implementation of Brainstorming Technique could improve the students’ ability of writing narrative text by the second year students of English Department of State Islamic University SUSKA Riau.